DEVELOPMENT OF LOW-CARBON GEOPOLYMER CONCRETE USING FLY ASH AND INDUSTRIAL SLAG AS SUSTAINABLE MATERIAL ENGINEERING - Edward Ngii; Dulguun Amarsaikhan; Fatima Al-Said; Khaled Al-Sharqi (Scientechno: Journal of Science and Technology, 2025)
The construction industry is a major contributor to global carbon emissions, with traditional Portland cement production accounting for approximately 8% of total CO? output. The development of low-carbon alternatives is essential to achieving sustainability goals and reducing the environmental footprint of infrastructure. This research focuses on developing geopolymer concrete using fly ash and industrial slag as sustainable raw materials, offering a viable substitute for ordinary Portland cement. The objective of the study is to evaluate the mechanical performance, durability, and carbon footprint reduction potential of geopolymer concrete mixtures under varied proportions of fly ash and slag. A quantitative experimental method was employed, involving the synthesis of multiple mix designs with differing binder ratios, followed by compressive strength testing, microstructural analysis, and lifecycle assessment (LCA). The results indicate that the optimal blend of 60% fly ash and 40% slag achieved a 42% reduction in carbon emissions compared to conventional concrete while maintaining a compressive strength exceeding 45 MPa after 28 days of curing. The inclusion of slag significantly enhanced early strength development and chemical stability due to calcium enrichment, while the use of fly ash contributed to long-term durability. The study concludes that fly ash–slag–based geopolymer concrete represents a promising low-carbon alternative, combining industrial waste valorization with superior structural performance. Future applications could advance sustainable material engineering practices in both civil and environmental infrastructure sectors.